ISSUES OF DEVELOPING POP SINGING IN MUSIC EDUCATION BASED ON THE DEVELOPMENT STRATEGY OF THE NEW UZBEKISTAN (Web of Teachers: Inderscience Research, 2026)
Today, Uzbekistan has entered a new stage of development. The New Uzbekistan Development Strategy focuses on spiritual and educational reforms and the comprehensive development of the potential of young people, enriching them intellectually and aesthetically, as one of its main areas. It was on this perspective that a new stage of music education, in particular, in the field of culture and art, which meets modern requirements, began. The development of pop singing performance plays an important role not only in bringing out the talents and creative potential of the younger generation, but also in raising the aesthetic taste of society and widely promoting national values and cultural treasures. This article discusses the development of modern performance of pop singers, practical issues, current problems and best practices in the integration of the development strategy of Uzbekistan and music education.